A group decision model for credit granting in the financial market - Paulo Cesar Schotten; Danielle Costa Morais (Financial Innovation, 2019)
Group decision models that contemplate the particularities of the decision-making process help organizations pursue their strategic objectives. In the financial market, the primary interest of organizations consists in ensuring financial returns, which guarantee stability for the organization. This study identifies major problems in the current process of credit granting in the financial market and argues the need for automatizing the organizational decision process while respecting the autonomy of decision-makers. To this end, this study proposes a group decision model based on the Strategic Choice Approach (SCA) for granting credit in a financial market organization. The results show that the adoption of the proposed model offers considerable gains in terms of organizational goals, transparency of the decision-making process, security for decision-makers, and reduction of organizational conflicts.
Keywords: 650; Group decision; financial organization; Strategic choice approach; Credit granting; Strategic decision-making